New economic policy and the birth of Malaysia’s own industrial relations system - Idrus, Durrishah (Faculty of Management and Human Resource Development, 2003)
This article explores the era of New Economic Policy (1971 - 1990) and its impact on the development of Malaysia industrial relations system. It examines factors that influenced the direction of the system and discusses how the controversial masterplan shaped and later established the present industrial relations system